2022
DOI: 10.1159/000524624
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin-Like 1 and Family with Sequence Similarity to 19 Member A5 Levels Are Decreased in Obese Children and Associated with Glucose Metabolism

Abstract: Introduction: Childhood obesity is a significant and growing problem worldwide. Recent evidence suggests Follistatin-like 1 (FSTL1) and family with sequence similarity to 19 member A5 (FAM19A5) to be novel adipokines. However, very few studies have examined the plasma levels of FSTL1 and FAM19A5 in children. Therefore, this cross-sectional study evaluated the association between serum FSTL1 and FAM19A5 levels with obesity in children and investigated the relationship between FSTL1 and FAM19A5 and glucose metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Negative correlations were detected between FAM19A5 and BMI as well as FBG and fasting insulin. 92 Inversely, it was found that serum FAM19A5 concentrations in T2DM patients were higher than that in non-diabetic subjects, and positively correlated with WC, WHR, FBG and HbA 1c. 93 What we can see is that FAM19A5 is so novel that there are few researches about it.…”
Section: Clinical Studiesmentioning
confidence: 94%
“…Negative correlations were detected between FAM19A5 and BMI as well as FBG and fasting insulin. 92 Inversely, it was found that serum FAM19A5 concentrations in T2DM patients were higher than that in non-diabetic subjects, and positively correlated with WC, WHR, FBG and HbA 1c. 93 What we can see is that FAM19A5 is so novel that there are few researches about it.…”
Section: Clinical Studiesmentioning
confidence: 94%
“…These results suggest an association of the FAM19A5 protein with metabolic disorders and emphasize its suggested positive effects on the body. 32 …”
Section: Fam19a5 Original Direction Of Researchmentioning
confidence: 99%
“…These results suggest an association of the FAM19A5 protein with metabolic disorders and emphasize its suggested positive effects on the body. 32 The first data on FAM19A5 genes comes from 2004. Y. Tom Tang et al then discovered a family of small secreted proteins in Homo sapiens and Mus musculus.…”
mentioning
confidence: 99%